2017
DOI: 10.2174/1568026617666170713172331
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Temporal Changes in Urine-based Metabolomic and Kidney Injury Markers to Detect Compound Induced Acute Kidney Tubular Toxicity in Beagle Dogs

Abstract: Urinary protein biomarkers and metabolomic markers have been leveraged to detect acute Drug Induced Kidney Injury (DIKI) in rats; however, the utility of these indicators to enable early detection of DIKI in canine models has not been well documented. Therefore, we evaluated temporal changes in biomarkers and metabolites in urine from male and female beagle dogs. Gentamicin- induced kidney lesions in male dogs were characterized by moderate to severe tubular epithelial cell degeneration/necrosis, epithelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 0 publications
3
18
1
Order By: Relevance
“…Species differences, sample size, and different mechanisms of renal toxicity are possible explanations for the seemingly later induction of uKIM-1 in our study. However, it has also been suggested that uKIM-1 may not be as sensitive and early a marker of AKI in dogs compared to humans (47,48). Urinary uKIM-1/uCr and absolute uKIM-1 concentrations in healthy dogs in our study were lower than reported previously, also in one study using the same assay (33,49).…”
Section: Discussioncontrasting
confidence: 69%
“…Species differences, sample size, and different mechanisms of renal toxicity are possible explanations for the seemingly later induction of uKIM-1 in our study. However, it has also been suggested that uKIM-1 may not be as sensitive and early a marker of AKI in dogs compared to humans (47,48). Urinary uKIM-1/uCr and absolute uKIM-1 concentrations in healthy dogs in our study were lower than reported previously, also in one study using the same assay (33,49).…”
Section: Discussioncontrasting
confidence: 69%
“…KIM-1 upregulation has been shown to correlate with damage to the proximal tubule in both acute and chronic kidney diseases [18,19,20,21,22]. We have previously reported an induction of KIM-1 in proximal tubules of diabetic ZD rats [11,13,23].…”
Section: Resultsmentioning
confidence: 99%
“…In dogs with leishmaniasis, characterized by glomerular mesangial proliferation and interstitial nephritis, urinary clusterin was elevated in more advanced renal cases 38 . Gentamicin-induced tubular necrosis also resulted in an increase in urinary clusterin in beagles, suggesting that tubular dysfunction alone can cause increased urinary levels of this protein 39 . In the current study, the elevation in urinary clusterin in sea lions suggests a similar urinary clusterin response is conserved in sea lions experiencing renal compromise.…”
Section: Leptospirosismentioning
confidence: 99%